Co-creating a strategy for transforming person centred cultures - Tuqiri, Karen; Murray, Suzanne; Shaw, Dan; Hackett, Kate; McCance, Tanya (Frontiers in Health Services, 2025)
IntroductionTransforming healthcare systems to support person-centred practice reflects environments where individual values and beliefs are respected and where healthful cultures can flourish. However, there are significant challenges within healthcare systems that impact on the development of healthful workplace cultures. The nursing and midwifery professions need to play an influential role in formulating health policy and decision-making to contribute to health and social care systems that are underpinned by person-centredness. This paper reports the use of a practice development approach underpinned by the Person-Centred Practice Framework to co-create a strategy for nurses and midwives that will enable the development of person-centred healthcare practices. The key objectives are to demonstrate the processes that support co-creation to build consensus on what is strategically important to nurses and midwives; to gain an understanding of the value of external facilitation throughout the process and exploring the challenges encountered during the development of the strategy.MethodsPractice Development methodology was the approach used with skilled facilitation adopted to enable the working with values and beliefs, defining purpose and vision and establishing agreed working principles and behaviours. Consensus building methods were used to co-create draft strategy priorities further defined by wider stakeholder engagement.ResultsA 5-year strategy was co-created with senior nursing and midwifery leaders, inclusive of key strategic priority areas and strategic actions. The seven priority areas align to the Person-Centred Practice Framework with underpinning shared purpose and values. (1) Developing Person-Centred Cultures, (2) Creating a Supportive Practice Environment, (3) Building Research Capacity, (4) Building a Dynamic Workforce, (5) Fostering Leadership at all Levels, (6) Enhancing Digital Informatics and New Technologies, (7) Delivering High Quality, (8) Safe Person-Centred Care. Together they provide a roadmap for implementation across the many nursing and midwifery contexts providing a solid foundation for leading and supporting person-centred practice across a large local health district with a focus on what matters most while continuing to be innovative in approaches to practice. The development of a clear shared purpose of person-centred practice and the exploration of values were critical first steps in the development of the strategy and provided a clear foundation from which the nursing and midwifery leaders could utilise for the ongoing strategic priorities and action discussions.Implications for practiceThe development of nursing and midwifery strategy using Practice Development Methodology and the Person-centred Practice Framework enables critical dialogue that supports nursing and midwifery leaders identify key influences over nursing and midwifery practice. This approach not only fosters a sense of ownership and engagement among nurses and midwives but also ensures that their values, beliefs, and professional insights are integral to the strategic direction of healthcare practices. By aligning the strategy with the Person-Centred Practice Framework, nurses and midwives are better able to develop a shared understanding of person-centred practice where the individual needs and preferences of patients, families and staff are acknowledged. Overall, this strategy represents a significant step forward in supporting the professional development of nurses and midwives, enhancing the quality of patient care, and fostering a healthful culture where continuous improvement and innovation are at the forefront of the healthcare system.